2020
DOI: 10.1055/a-1152-4662
|View full text |Cite
|
Sign up to set email alerts
|

Herzinfarktsterblichkeit innerhalb und außerhalb der Kliniken in Berlin

Abstract: Zusammenfassung Ziel der Studie Die Sterblichkeit am Herzinfarkt setzt sich zusammen aus den außerhalb und innerhalb der Klinik Verstorbenen. Da es sich beim Herzinfarkt um eine schwerwiegende Erkrankung handelt, ist der Anteil an Patienten, die vor Krankenhausaufnahme versterben, vergleichsweise groß und wie Daten aus Schweden und Augsburg zeigen in seiner relativen Häufigkeit bezogen auf al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, this presumption is difficult to verify, as studies on pre-hospital AMI mortality are scarce, and often small-scaled. A German study reported that in Berlin 66% of AMI deaths occurred outside the hospital [ 30 ], while an earlier study from the U.S. reported a share of 60% pre-hospital AMI deaths in Worcester, Massachusetts [ 31 ]. In rural areas, which are more prevalent in the U.S. than in Germany [ 32 ], the share of pre-hospital AMI deaths might be even higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, this presumption is difficult to verify, as studies on pre-hospital AMI mortality are scarce, and often small-scaled. A German study reported that in Berlin 66% of AMI deaths occurred outside the hospital [ 30 ], while an earlier study from the U.S. reported a share of 60% pre-hospital AMI deaths in Worcester, Massachusetts [ 31 ]. In rural areas, which are more prevalent in the U.S. than in Germany [ 32 ], the share of pre-hospital AMI deaths might be even higher.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of VF and SCD in the context of MI (65% and 41%, respectively), mostly during or within minutes after acute MI (acute LAD occlusion), was comparatively high in our pig cohort. Calculations of out‐of‐hospital‐mortality for patients with acute MI vary between 9% and 35%, 64 , 65 , 66 adding to the 1.2% risk of SCD in the first month and each following year after survived MI. 6 The fact that VF and SCD occurred around LAD occlusion in IHF pigs and in none of the control pigs (especially not during the invasive diagnostic catheter examination) suggested ischemia as the key trigger of VF in our model.…”
Section: Discussionmentioning
confidence: 99%